Pendampingan Ibu dalam Pembuatan Makanan Berbasis Ikan Teri dan Buah Merah untuk Pemenuhan Gizi dan Pemantauan Peningkatan Berat Badan Balita - Christina Tien Popang; Ketrina Misiro; Diana Ode; Siti Mardiana; Ferdiana Ludiantini Refwutu; Yuliance Adi; Eni Maria D. Rumpumbo Rumpumbo (Jurnal Pengabdian Ilmu Kesehatan, 2025)
The assistance provided to mothers in the preparation of meals based on anchovies and red fruits for fulfilling the nutrition of toddlers (24–60 months) and monitoring their growth in relation to weight gain in the working area of Puskesmas Sanoba aims to improve the nutritional status and growth of toddlers. This activity was conducted as a response to the issues of malnutrition and undernutrition still present in the area. Anchovies and red fruits were chosen as highly nutritious food ingredients rich in protein, healthy fats, and vitamins, all of which are essential to support the growth and development of toddlers. The assistance to mothers was carried out through training on preparing nutritious meals using these two ingredients, as well as educating them about the importance of a balanced diet. Furthermore, growth monitoring was conducted to assess the effect of these meals on toddlers' weight gain. The results of the activity indicated an improvement in nutritional status and weight in most of the toddlers who participated in the assistance. Although some toddlers showed slower progress, overall, the program successfully had a positive impact on the fulfillment of nutrition and the growth of children. This assistance also increased mothers' knowledge about the importance of providing nutritious food and raised awareness of their active role in meeting their children's nutritional needs. This program is expected to serve as a model in efforts to improve the nutritional status of toddlers in other areas.